2013
DOI: 10.3844/ajeassp.2013.327.339
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Low-Density Biomass Feeding System for Fluidized Bed Gasifiers

Abstract: For efficient operation of a biomass gasifier, the biomass material must be fed continuously to the system. A feeding system for chopped straw and rice husk was designed, constructed and evaluated. It consisted of: A frame, a hopper, an auger, two agitators, a drive system and a power unit. Initial testing showed that wheat straw and rice husk, being highly cohesive materials, created tunnel flow and piping conditions. This occurs when the pressure above an impending dome of material is too small resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Regarding rice straw cutting length, Ghaly et al. (2013) stated that the length of straw ranged from 14.49 to 18.85 mm, relying on the cutting speed and cutting depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding rice straw cutting length, Ghaly et al. (2013) stated that the length of straw ranged from 14.49 to 18.85 mm, relying on the cutting speed and cutting depth.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding rice straw cutting length, Ghaly et al (2013) stated that the length of straw ranged from 14.49 to 18.85 mm, relying on the cutting speed and cutting depth. On the other side, El-Sayed et al (2013) and El-Khateeb (2001) reported that increasing cutter speed from 500 to 1500 rpm increases the percentage of cutting length in the range (0.2 cm) by (54-93%).…”
Section: Introductionmentioning
confidence: 99%
“…It has a secondary distributor plate in the spout region above the secondary column. The biomass material is fed into the secondary column by specially designed straw feeder by Ghaly et al [23]. By the virtue of its design, the dual distributor fluidized bed ensures a more homogeneous mixture of biomass and bed materials since the biomass is pneumatically introduced through the bottom center of the reactor by the secondary column.…”
Section: The Dual-distributor Fluidized Bed Gasifiermentioning
confidence: 99%